Pengaruh Islam dalam silsilah Raja-Raja Jambi sebagai karya historiografi islam Jambi abad ke 19-20 - El-Quraisy, Saidina Usman (2016)
Research on the history of Islam in Nusantara will also include research on Malay Islamic literatures, especially those having historical characteristics. But the researchers on the history of the Malay world from the West mostly investigate the pre-Islamic tradition and culture. Yet Islamic Malay historiography which includes historical texts from 13th until the 20th century is an important historical source which needs to be investigated immediately. Such tendency reflects the stance of Orientalists who do not want to accept and acknowledge the Malay intellectual legacies as historiographical works which can be used as one of the Islamic historical sources in Nusantara. Such research needs to be done because the facts written in the Islamic Malay historical works can benefit and give true understanding of Islamic history which are investigated through the sources written by Muslim scholars in Malay-Indonesian archipelago. To get a true understanding of Islamic history in Jambi, the research on Jambi Islamic historiography needs an analysis of Islamic elements which give a great impact on the text of Silsilah Raja-Raja Jambi (Genealogy of Jambi kings). In addition to investigating the elements of belief, politics, and Islamic law, this research also investigates the impact of other elements such as Arabic and Jawi script written in the text. Furthermore by means of comparing the other historical texts and analyzing the characteristics of Malay historiographical works, this research proves that the text of Silsilah Raja-Raja Jambi is a Jambi-Malay Islamic historiographical work.